Hierarchy Models of City Size: An Economic Evaluation - J.V. Henderson (Queen's University, Department of Economics, 1972)
In this paper, the Losch-Beckmann hierarchy model of city size is evaluated in terms of its economic content and consistency. It is shown that the model violates basic economic principles. Consequently, an alternative framework is outlined, and for a simple example the properties of the model are examined.
Keywords: 330